Curcumin as an Amyloid-indicator Dye in E. coli - McCrate, Oscar A. (2013)

(untitled)
We have demonstrated that curcumin is an amyloid-specific dye in E. coli. Curcumin binds to curliated whole cells and to isolated curli amyloid fibers. Similar to Congo red, curcumin exhibits a red-shift in absorbance and a significant increase in fluorescence upon binding to isolated curli.